Impact of Service-Learning on Communication Skills Development of Students of Vocational Schools - Rukhsana Ahmad; Sarwat Begum; Iqbal Ahmad (Development in Language Studies, 2022)
Service-learning is a promising and effective strategy to achieve the goals of facilitating communication skills development among students. However, there are many issues remain unexplored related to the role of service-learning regarding the communication skills improvement of vocational and technical students. This study was conducted to explore the impact of service-learning on the communication skills development of undergraduate students in vocational training schools in Punjab Pakistan. Data was collected from 213 students of vocational institutes who participated in the service-learning course using a survey questionnaire. the data was analyzed using descriptive statistical techniques and ANOVA. The analysis showed that service-learning positively contributed towards the students’ course knowledge. However, most of the students replied that it did not improve their communication skills or problems solving skills which are essential academic skills. The study further revealed that there was no significant difference in the perceptions of male and female students about the contributions of service-learning towards the communication skills development of students. The study results provide new pertinent information to management and teachers at vocational institutes about the benefits of service-learning as a language enhancement pedagogy. Based on the results, it is suggested that the findings of this study may be tested in other cultural contexts for further understanding the implementation of service-learning in language classes.